The Effectiveness of Cognitive Behavioral Therapy on Psychological Symptoms and Psychological Hardiness in Single-Parent Adolescents - Farrashzadehjelodar, Rozita; Sadeghi, Jamal (Mental Health and Lifestyle Journal, 2024)
The present study aimed to determine the effectiveness of cognitive behavioral therapy (CBT) on psychological symptoms and psychological hardiness in single-parent adolescents. This study employed a quasi-experimental method using a pretest-posttest design with one experimental group and one control group. The statistical population consisted of single-parent adolescents referred to counseling centers in Babol in 2023. The sample included 30 single-parent adolescents who were selected using purposive non-random sampling and then randomly assigned to either the experimental group (n = 15) or the control group (n = 15). Data were collected using the Psychological Symptoms Questionnaire and the Psychological Hardiness Questionnaire. Subsequently, cognitive behavioral therapy was administered to the experimental group in eight 90-minute sessions. After the completion of the CBT sessions, a posttest was conducted for both the experimental and control groups. The findings showed that the mean scores of psychological symptoms and psychological hardiness in the posttest of the experimental group were significantly different compared to the pretest. Therefore, cognitive behavioral therapy has an effect on psychological symptoms and psychological hardiness in single-parent adolescents.